Technology Legitimation: A Product‐Level Examination Across the Technology Lifecycle. (10th November 2021) - Bunduchi, Raluca; Candi, Marina
Abstract: Legitimacy is an important explanatory factor for the success or failure of new products, but how individual actors engage in legitimation is not well understood. We focus on two categories of actors: the firms that develop and commercialize new technology‐based products and the customers who evaluate these products and examine their legitimation behaviour across the technology lifecycle. Drawing from organization research, innovation studies and product innovation literatures, we posit that firms' legitimacy‐seeking behaviour varies across the technology lifecycle depending on the need for legitimacy in each stage, while customers' emphasis varies depending on the relative importance they ascribe to each type of legitimacy. We test these hypotheses by examining online data about products that span four stages of the technology lifecycle. We advance a micro‐level understanding of technology legitimation by demonstrating that firms' efforts to seek legitimacy and customers' emphasis on legitimacy for new technology‐based products are distinct phenomena underpinned by different mechanisms. We expand the scope of existing technology legitimation research by examining how firms' efforts and customers' emphases vary across the technology lifecycle.